Study of etiological factors, clinical profile and outcomes of the non-traumatic acute abdomen in adult patients - Meena, Jyoti; Patel, Rahul; Datey, Ashirvad (International Surgery Journal, 2025)
Background: Acute abdomen is the most prevalent surgical emergency. The natural history of acute abdomen is contingent upon the underlying disease process, which may, in some cases, resolve spontaneously with or without intervention, while in others, it may advance to widespread peritonitis and mortality. The need of this research is to conduct a clinical audit of patients with non-traumatic acute abdomen to facilitate early detection and prompt care. Objectives were to investigate the etiological causes, clinical characteristics, and outcomes of non-traumatic acute abdomen. Methods: Descriptive research conducted in a tertiary teaching hospital over an 18-month period (November 2022 to April 2024). Patients with acute abdomen requiring over 24 hours of observation or inpatient treatment in the surgical wards were included. The diagnosis was established by clinical and investigative findings and then validated during laparotomy in the operated patients. Results: The 123 eligible patients were picked up to participate in the study. Surgical management was done in 67.5% cases and 32.5% were managed conservatively. The 98.4% cases were discharged whereas mortality was documented in 1.6% cases. Conclusions: The diversity in presentations and underlying causes emphasizes the crucial role of prompt and accurate diagnosis. Low mortality rate (1.6%) and relatively short hospital stay (average 6.8 days) suggest the effectiveness of this targeted approach. In conclusion, this study highlights the diverse presentations and underlying causes of non-traumatic acute abdomen. By considering the specific aetiology and tailoring treatment accordingly, healthcare professionals can ensure prompt and effective management of this complex condition.